Assessment of plant availability and environmental risk of biosolids-phosphorus in a U.S. Midwest Corn-Belt Soil. (1st May 2016) - Tian, G.; Cox, A.E.; Kumar, K.; Granato, T.C.; O'Connor, G.A.; Elliott, H.A.
Abstract: A field experiment was conducted from 2005 to 2008 in Fulton County, Western Illinois with biosolids from conventional wastewater treatment applied as corn fertilizer in a series of P rates (0, 163, 325, 488, 650 kg P ha −1 ) along with commercial P fertilizer - triple superphosphate P (TSP) as reference to assess biosolids-P plant availability and potential loss to waterbodies through runoff. Air-dried biosolids and TSP were incorporated into surface soil at end of 2005, and corn ( Zea mays) was planted for three consecutive years (2006–2008). Concentrations of soil extractable P except for Mehlich-3 P were always lower in the biosolids than TSP treatments at the same P rates. The soil potentially available P in water extractable P (WEP) and Olsen P derived from biosolids-P estimated by the exponential depletion model was 2–4% and 15–24% of total P in the applied biosolids, respectively. The residence time of biosolids-induced WEP and Olsen P in Midwest soil under annual corn cropping was 5 and 2 years, respectively. Corn tissue analysis showed lower increase in P concentration by biosolids-P than TSP. The elevation rate of soluble reactive P (SRP) concentration in simulated runoff was less by biosolids than TSP. Based on the data in this study, the plant availability and environmental risk of biosolids-P are lower than those of TSP in the Midwest soil, thus use of biosolids as P nutrient for corn would not cause a major impairment to water sources even P applied through biosolids was not completely used by annual crop. Highlights: Biosolids-phosphorus was of low extractability in the Midwest soil. Biosolids-P application did not cause the soluble P spike in soil. Phytoavailability was lower for biosolids-P than triple superphosphate (TSP). Elevation of runoff soluble reactive P by biosolids-P was less than that by TSP. Phosphorus in biosolids from wastewater treatment has a low environmental risk.